The Idea of School Teacher in the National Education Policy 2020 - Gulati, Nidhi; Jain, Manish (JOURNAL OF INDIAN EDUCATION, 2022)
This paper analyses the idea and conception of the school teacher in India’s National Education Policy (NEP) 2020. It explains the various reasons discussed in the research studies and the National Education Policy to assign a centrality to the school teacher in order to bring educational reform. The article examines the idea of the school teacher through the lens of NEP 2020 considering four frames of reference namely language schism, community, incentivisation and performance to discuss the construct of the teacher in NEP 2020.